REPEAT AFTER ME: THE VALUE OF REPLICATION - Macaulay, Ronald (International Journal of English Studies, 2003)
The past forty years have seen a variety of sociolinguistic investigations, producing interesting results. However, there is always a risk that some of these results may have given a misleading picture of the situation because of a design flaw in the project or some effect of ignored factors. One way of testing any claims is through a replication of the original study. This paper examines three claims made about discourse variation, showing how separate studies can either support or challenge those claims.